2013
DOI: 10.1155/2013/419092
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects the Brain of Obese Mice from Oxidative Damage

Abstract: Resveratrol (3,5,4′-trihydroxy-trans-stilbene) is a polyphenolic phytoalexin that exerts cardioprotective, neuroprotective, and antioxidant effects. Recently it has been shown that obesity is associated with an increase in cerebral oxidative stress levels, which may enhance neurodegeneration. The present study evaluates the neuroprotective action of resveratrol in brain of obese (ob/ob) mice. Resveratrol was administered orally at the dose of 25 mg kg−1 body weight daily for three weeks to lean and obese mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 46 publications
1
27
1
Order By: Relevance
“…In a STZ-treated rat model of diabetes, resveratrol slowed diabetes-induced neurodegeneration by decreasing both astrocytic activation and secretion of pro-inflammatory mediators like TNFα in the rat hippocampus (Jing et al, 2013). In another study examining oxidative nerve damage in lean and obese mice, resveratrol blocked the obesity-specific increases in LPO and upregulated antioxidant activity (Rege et al, 2013). Finally, in an earlier study of primary midbrain neuron-glia rat tissue cultures, resveratrol provided dopaminergic neuroprotection by inhibiting MGLA in lipopolysaccharide-induced neurotoxicity (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a STZ-treated rat model of diabetes, resveratrol slowed diabetes-induced neurodegeneration by decreasing both astrocytic activation and secretion of pro-inflammatory mediators like TNFα in the rat hippocampus (Jing et al, 2013). In another study examining oxidative nerve damage in lean and obese mice, resveratrol blocked the obesity-specific increases in LPO and upregulated antioxidant activity (Rege et al, 2013). Finally, in an earlier study of primary midbrain neuron-glia rat tissue cultures, resveratrol provided dopaminergic neuroprotection by inhibiting MGLA in lipopolysaccharide-induced neurotoxicity (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…61 In the same line, RSV has been reported to normalize GSH or MDA levels in a rat model of spinal cord injury 62 or in the brain of obese mice. 63 Since the discovery of sirtuin-activating compounds such as RSV, 4 a rich controversy exists regarding the direct path via SIRT1 or via an indirect modus operandi of these compounds. 34 A recent and elegant study has shed some light on the debate and demonstrated that SIRT1 is directly activated by RSV, through an allosteric mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…All these compounds show excellent antioxidant activities and beneficial effects in preventing oxidative stress, mitochondrial dysfunction and inflammation in the experimental models of neurodegenerative disorders (Calabrese et al, 2012; Lee et al, 2015; Li et al, 2014; Nataraj et al, 2015; Rege et al, 2013; Singhal et al, 2013; Subash et al, 2014a, 2014b, 2015; Tapias et al, 2014; Vauzour, 2012; Vepsäläinen et al, 2013; Wang et al, 2014]. One of the well-known polyphenols is resveratrol (3, 5, 4’-trihydroxy-trans-stilbene) contained in red grapes and it has been shown to protect the brain from oxidative damage (Gacar et al, 2011).…”
Section: Translational Research Opportunities and Challengesmentioning
confidence: 99%